Population distribution and population growth in Yogyakarta special region - Ida Bagus Mantra (Indonesian Journal of Geography, 1986)
The Sultanate of Yogyakarta which, during the struggle for independence and subsequently has been known as the Special Region of Yogyakarta, is located in the southern part of Central Java. It constitutes much of the heartland of Javanese culture, for Yogyakarta was the center of the pre-colonial Kingdom of Mataram.Within Yogyakarta Special Region, there is a marked contrast in the population density between Bantu! and Sleman regencies on one hand, and Gunung Kidul and Kulon Progo on the other hand. The basic reason for this difference is the fact that the soil of Bantul and Sleman regencies is primarily young and vulcanic, while there is also a good water supply and intensive irrigation network.The annual rate of population growth in Yogyakarta Special Region is much lower compared with other provinces in Java. During 1961 and 1971 the rate of population growth was 1.1 percent, for the period 1971— 1980 became 1.09 percent. This region experienced a net loss of population through migration, and that the losses were greater in the poor areas of Gunung Kidul and Kulon Progo